The importance of surrounding the athlete`s heart with a team - Dean, P. N.; Pugh, K.; Statuta, S. M.; MacKnight, J. M. (Clinics in Sports Medicine, 2022)
Providing medical care for an athlete can be challenging in many aspects. One specific aspect is the athlete`s cardiovascular system. Athletic training and physical activity certainly can improve cardiovascular health, but it can also cause cardiac adaptations and place athletes at risk for sudden cardiac arrest. When an athlete has cardiac symptoms, a concerning family history, abnormal cardiac testing, or an underlying cardiac condition, a wide range of professionals are needed to appropriately care for the athlete under evaluation.